2017
DOI: 10.1017/wsc.2017.66
|View full text |Cite
|
Sign up to set email alerts
|

Seed Dormancy and Seed Morphology Related to Weed Susceptibility to Biofumigation

Abstract: Biofumigation is practiced to control soilborne pests and weeds in agronomic fields. The objectives of this research were to assess the dose response of weed seeds to Indian mustard biofumigation and associate responses to seed dormancy state, initial dormancy, and seed parameters. A petri dish biofumigation methodology was developed to expose seeds of common lambsquarters, bird vetch, wild carrot, common ragweed, green foxtail, velvetleaf, hairy galinsoga, and red clover to allelochemicals produced after rehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 44 publications
2
30
1
Order By: Relevance
“…Different responses observed between years and sites may be explained by the variability of the biofumigant potential and biofumigation conditions, but also by the intra-and interspecific vulnerability of weeds to the allelochemicals released during biofumigation. Previous work showed that weed seed susceptibility to biofumigation allelochemicals differed according to seed dormancy, seed size and testa thickness (Lefebvre et al, 2018). Furthermore, as PCoAs considered individual weed species responses to treatments, species composition of the weed community in each site may partly explain the difference between sites.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Different responses observed between years and sites may be explained by the variability of the biofumigant potential and biofumigation conditions, but also by the intra-and interspecific vulnerability of weeds to the allelochemicals released during biofumigation. Previous work showed that weed seed susceptibility to biofumigation allelochemicals differed according to seed dormancy, seed size and testa thickness (Lefebvre et al, 2018). Furthermore, as PCoAs considered individual weed species responses to treatments, species composition of the weed community in each site may partly explain the difference between sites.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were prepared for HS GC‐MS as described in Lefebvre et al . (). Volatile organic probes were also analysed via thermal desorption–gas chromatography.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations